2019
DOI: 10.1186/s12969-019-0304-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery dilation associated with anti-synthetase syndrome in an adolescent

Abstract: BackgroundIdiopathic inflammatory myopathies (IIM) are a group of systemic autoimmune disorders primarily affecting skeletal muscle. Pediatric coronary artery dilation is frequently discussed in Kawasaki disease. However, it has yet to be reported in the IIMs or antisynthetase syndrome. We report a unique case of a patient with IIM, antisynthetase syndrome and coronary artery dilation.Case presentationWe report an adolescent presenting with joint symptoms, fever, and eye swelling with a clinical diagnosis of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our index case never followed the sequence and only had coronary artery abnormalities (CAA) without compatible clinical and laboratory feature which was perplexing to us. Occasional cases of mild CAA (2.5-5 Z score) have been reported in non-KD febrile illness but moderate CAA have never been [2][3][4]. The presence of moderate CAA rules out non-KD febrile illness in our case.…”
mentioning
confidence: 53%
“…Our index case never followed the sequence and only had coronary artery abnormalities (CAA) without compatible clinical and laboratory feature which was perplexing to us. Occasional cases of mild CAA (2.5-5 Z score) have been reported in non-KD febrile illness but moderate CAA have never been [2][3][4]. The presence of moderate CAA rules out non-KD febrile illness in our case.…”
mentioning
confidence: 53%
“…A study has shown that Raynaud's phenomenon increased the chance of coronary vasospasm (46). One child with JDM was reported to have coronary artery dilatation which was an unusual finding (47).…”
Section: Delayed Onset Cardiac Diseases In Children With Juvenile Der...mentioning
confidence: 99%
“…Other than the classic features mentioned above, calcinosis, panniculitis, coronary artery dilatation, eosinophilic pleural effusions, and myopericarditis have also been reported in small case series. [60][61][62][63][64][65][66][67][68][69]…”
Section: Other Accompanying Featuresmentioning
confidence: 99%